Correlation of motor function with transcallosal and intracortical inhibition after stroke - Takeuchi, N; Tada, T; Toshima, M; Ikoma, K (Journal of rehabilitation medicine, 2010)
The inhibitory role of neuronal networks in motor recovery after stroke remains to be elucidated. We examined the influence of transcallosal inhibition and short intracortical inhibition on motor recovery after stroke. We also investigated the correlation between transcallosal inhibition and mirror activity. A cross-sectional study. Thirty-eight chronic stroke patients. Transcallosal inhibition was evaluated using single transcranial magnetic stimulation, and short intracortical inhibition was assessed using paired-pulse transcranial magnetic stimulation. Mirror activity was measured during tonic contraction of the contralateral hand. Transcallosal inhibition from the contralesional to the ipsilesional motor cortex correlated positively with motor function of the paretic hand; in contrast, transcallosal inhibition to the ipsilesional motor cortex correlated negatively with mirror activity of the paretic hand in both cortical and subcortical stroke patients. Short intracortical inhibition of the ipsilesional motor cortex correlated negatively with motor function of the paretic hand in only the subcortical stroke patients. Transcallosal inhibition from the contralesional to the ipsilesional motor cortex may inhibit mirror movements in stroke patients with good motor function. The weak transcallosal inhibition in patients after stroke with poor motor function may be ineffective for inhibiting mirror movement; however, it may have the advantage of facilitating motor recovery.